A nano-electrospray investigation into the subunit exchange of small heat shock proteins - Benesch, J; Sobott, F; Vierling, E; Robinson, C (2002)
The use of nano electrospray ionization (ESI) data for the subunit exchange of small heat shock proteins (sHSP) is discussed. The sHSP are maintained intact through the mass spectrometer using appropriate solution conditions, and careful control of gas-phase parameters. The mixtures of HSP16.9 and 18.1 are examined, both after equilibration and in real-time immediately after mixing. A comparison with the spectra indicates that after equilibration, the distribution of the hetero-complexes is governed by the starting ratio of the two components.